Antecendents of Self Efficacy and its Influence on Lecturer Performance - Windayati, Diana Titik; Onoyi, Nona Jane; Kurniawati, Ely; Yanti, Sri (CV ODIS, 2024)
Abstract. As an educator, lecturers must have competence in carrying out their duties through the Tri Dharma of Higher Education. This study examines the Antecendent Self Efficacy and its Effect on Lecturer Performance. In this study, the population was private university lecturers in Batam and the sample was 122 permanent lecturers. The approach of quantitative research methods, questionnaires distributed to respondents as a way of collecting data. The result is that the three variables, competence, motivation and work engagement on performance have a positive and insignificant effect, while on self efficacy, competence has a positive and insignificant effect, motivation and work engagement have a significant positive effect on self efficacy, and self efficacy has a positive and insignificant effect on performance.